FORMULASI DAN UJI EFEKTIVITAS SEDIAAN ROLL ON AROMATERAPI BERBAHAN AKTIF MINYAK ATSIRI DAUN JERUK NIPIS (Citrus aurantifolia) SEBAGAI RELAKSASI PADA KELINCI ANGGORA (Oryctolagus cuniculus domesticus) - Ferliano Miko Fachriansyah; Riana Putri Rahmawati; Fahrudin Arif (Yayasan Nusantara Hasana Berdikari, 2025)
Anxiety disorder is a mental condition characterized by excessive feelings of fear and worry. Individuals experiencing this disorder may feel anxious almost constantly, which can interfere with their daily lives. Aromatherapy is a therapeutic practice that utilizes essential oils extracted from plant parts—typically through distillation—to enhance physical and emotional well-being. The development of aromatherapy as a treatment can be applied to roll-on formulations due to their convenient and practical use, aligning with public preference. This study aims to evaluate the physical quality and effectiveness of an aromatherapy roll-on preparation containing lime leaf (Citrus aurantifolia) essential oil for relaxation in Angora rabbits (Oryctolagus cuniculus domesticus). Physical quality assessments included homogeneity test, organoleptic evaluation, pH measurement, user preference test, and skin irritation test. Effectiveness testing was conducted based on varying concentrations (3%, 4%, 5%) and a control group. The collected data were processed using SPSS software, applying a one-way ANOVA. The findings revealed that all preparations were yellow liquids with the distinctive citrus aroma of lime essential oil. Homogeneity and pH tests confirmed that all formulations met the criteria for topical application. In terms of effectiveness, the 5% concentration yielded the most optimal results. Normality and homogeneity tests indicated that all data sets had normal and homogeneous distributions (p>0,05), fulfilling requirements for ANOVA. The ANOVA results showed a significant difference among the five treatment groups (p<0,05). Post Hoc analysis identified a significant difference between the negative control group and all other treatment groups (p<0,05).